International Network, Social Capital and the Role of Muhammadiyah During the 2006 Yogyakarta Earthquake - Muhammad Zahrul Anam; Sugito Sugito (Journal of Islamic World and Politics, 2021)
This article aims to investigate the impact of the international network and social capital on the effectiveness of Muhammadiyah’s emergency response in the 2006 Bantul earthquake. Despite paying more attention to religious and spiritual issues, Muhammadiyah, an Islamic-based social movement, plays a significant role in humanitarian issues. The 2006 earthquake in Bantul devastated public amenities, claimed thousands of people, and caused economic loss. The local government and private sectors of Bantul could not cope with the disaster. The most disaster-affected districts in Bantul Regency were Pundong, Bambanglipuro, and Jetis. Then, Muhammadiyah made an immediate emergency response to help those affected districts. In collaboration with overseas counterparts, Muhammadiyah collected humanitarian assistance. Muhammadiyah might not complete its humanitarian mission without the support of existing local Muhammadiyah in those districts. In other words, Muhammadiyah’s social capital is influential for humanitarian missions. This paper utilized two concepts to elaborate on the effectiveness of Muhammadiyah’s emergency response, namely transnational advocacy networks (TANs) and social capital. Then, this article argues that the higher level of TANs and social capital Muhammadiyah has, the more emergency response it can complete effectively. This paper discovered that three districts had different levels of TANs and social capital. In Pundong, the level of leverage politics (TANs) was higher than social capital. However, both Bambanglipuro and Jetis had a high level of social capital, whereas their leverage politics were low.